Ethnic And Political Conflicts In The Eastern Senatorial District Of Kogi State, Nigeria: Some Suggested Therapeutic Measures - Omede, Jacob (Advances in Social Sciences Research Journal, 2020)
This paper titled “Ethnic and political conflicts in the Eastern Senatorial Districts of Kogi State, Nigeria: Some suggested therapeutic measures” was an attempt to bring a relatively lasting solution to the incessant ethnic and political crises in the said senatorial district of the state. In an attempt to do this, the paper examined at the background the characteristics or nature of the Igala, Bassa and Ebira people who are the nationalities that are the original inhabitants of the land by pointing out how they lived harmoniously in the past. The paper in a further attempt to examine the causes of conflicts in this district had to do this in relation to Carl Max theory of conflict reviewed by Chappelow. The possible causes of ethnic and political conflicts in this area that the paper identified and discussed included land dispute, poverty and unemployment, loss of morality, desire to test and manifest “black power” as well as godlessness and bad politicking. The consequences of these which included the destruction of lives and properties, love lost, vendetta, vacation of ancestral homes as well as decline in commercial and agricultural activities were pointed out and also discussed. The paper concluded by recommending proper boundary delineation, more frequent political and moral education, formation of peace clubs as well as depoliticizing community policing and godly living as possible panaceas.